Lacticaseibacillus rhamnosus CA15 (DSM 33960) strain as a new driver in restoring the normal vaginal microbiota: A randomized, double-blind, placebo-controlled clinical trial - Rapisarda, Agnese Maria Chiara; Pino, Alessandra; Grimaldi, Raffaela Luisa; Caggia, Cinzia; Randazzo, Cinzia Lucia; Cianci, Antonio (Frontiers in Surgery, 2023)
Probiotics play a key role in maintaining the health of the female reproductive tract, representing a promising alternative to safeguard or restore the homeostasis of the vaginal microbiota. The present randomized double-blind placebo-controlled study was performed to evaluate the ability of the potential probiotic Lacticaseibacillus rhamnosus CA15 (DSM 33960) strain, orally administrated, to balance the vaginal microbiota of women with vaginal dysbiosis. Sixty women, with signs and symptoms of vaginal dysbiosis, were recruited and randomly allocated to receive oral capsules containing the L. rhamnosus CA15 (DSM 33960) strain at 1.0 × 1010 colony-forming units or placebo once daily for 10 days. Clinical and microbiological parameters were evaluated in three scheduled appointments: at baseline (T0), 10 days after the start of the treatment (T1), and 30 days after the end of the treatment (T2). In addition, the quality of life, through the WHO quality of life assessment questionnaire, was assessed at baseline (T0) and 30 days after the end of the treatment (T2). The probiotic was well tolerated and no side effects were reported. The oral consumption of the potential probiotic L. rhamnosus CA15 (DSM 33960) strain determined a significant improvement of both clinical signs and symptoms not only 10 days after the start of the treatment (T1) but also 30 days after the end of the treatment (T2). A significant reduction of potential pathogens and a concomitant increase of lactobacilli was revealed, by microbial count, at both T1 and T2 sampling times. In addition, the enhancement of the perceived physical health, social relations, and environment was reported. Differently, in placebo group clinical and microbiological parameters as well as quality of life remained almost unchanged. The potential probiotic L. rhamnosus CA15 (DSM 33960) strain could be a safe and effective approach to restore and maintain a balanced vaginal microbiota.